A 2-generated 2-related group with no non-trivial finite quotients - Ol’shanskii, A.Yu.; Sapir, M.V. (Algebra and Discrete Mathematics, 2007)
We construct a 2-generated 2-related group without non-trivial finite factors-groups. This answers a question of J.
Button.